A comprehensive review of approaches to defining key performance indicators for sustainable performance - Hendro Siswono; Arum Oktifani; Ananta Nasution; Iip Latipudin; Hernadewita (JENIUS : Jurnal Terapan Teknik Industri, 2026)
This study presents a systematic literature review aimed at identifying and analyzing Key Performance Indicator (KPI) determination methods in the context of sustainability performance measurement. A total of 56 peer-reviewed articles published between 2011 and 2025 were examined across various sectors including manufacturing, supply chains, organizations, and urban areas. This study employed a Systematic Literature Review approach. This review categorized the literature based on three main dimensions: first, the Triple Bottom Line (TBL) domains of economic, social, and environmental; second, the object level of individual, organization, process, and sector; and fourth, the tools or methods used for KPI determination, including the Balanced Scorecard, Analytical Hierarchy Process (AHP), Performance Prism, and literature-based approaches. The findings indicate that most studies focus on the organizational and supply chain levels, using various approaches for KPI selection and weighting. Although some studies integrate all TBL domains, there is still a gap in comprehensive measurement of social and environmental aspects. This review provides an overview of methodological trends in KPI determination for sustainability and identifies opportunities for developing more contextual and integrated models in future research.